WEB PORTAL-BASED MANAGEMENT INFORMATION SYSTEM FOR WEDDING ORGANIZER SERVICE RENTAL - hafidz arifanto; Alif Catur Murti; Rizkysari Meimaharani (LPPM Universitas Abdurrab, 2026)
Wedding Organizer (WO) provides specialized services that assist couples and their families from the planning stage to event implementation. However, the current WO service process still faces several issues, including manual information distribution, difficulty comparing service packages, lack of customer review history, and limited digital service marketing. These conditions create challenges for new WO businesses in gaining market visibility and hinder customers from selecting services based on quality and verified feedback. To address these problems, this study develops a Web Portal-Based Management Information System that enables users to access WO information, compare packages, make bookings, and submit reviews through an integrated platform. The system was developed using the Waterfall model, beginning with requirements analysis obtained through interviews and thematic analysis. System functionality was tested using Black-box Testing to ensure each feature operates according to specifications. The results show that all modules package comparison, booking and payment verification, partner management, and user review function correctly and support users in making more informed decisions. This system also improves WO visibility through digital-based service promotion.